Experientially based narrative instruction: A neurocognitive perspective. (October 2022) - Israelsen-Augenstein, Megan; Gillam, Sandi; Mecham, Jamie; Ashcroft, Hailey
Background: The purpose of this study was to evaluate the feasibility of a personal narrative intervention based on neurocognitive principles and experientially based learning for improving the personal narrative language abilities of a school-age child with Down's syndrome. Method: A single-case design using contemporary statistical techniques was employed to complete this study. The participant was 8 years 8 months at the time of the study and he participated in a 14-week personal narrative intervention. Personal narrative samples were collected at the beginning of each intervention session prior to instruction. Narrative samples were scored for narrative quality, language productivity, and lexical diversity. Results: As a result of the intervention, the participant demonstrated moderate-significant increases in narrative abilities for narrative quality, language productivity, and lexical diversity. Conclusions: The use of a personal narrative based on neurocognitive principles and experientially based learning may be feasible for improving the personal narrative language abilities of school-age children with Down's syndrome.